Management of foot rot of citrus (Citrus jambhiri spp.) using biocontrol agents - CHOUDHARY, AJAY KUMAR; SINGH, NARINDER; BUTTAR, DALJEET SINGH (The Indian Journal of Agricultural Sciences, 2022)
Citrus holds an important place in promoting the horticultural wealth and economy of India. Foot rot caused by Phytophthora spp. is a widespread problem of the citrus nursery. Citrus jambhiri, a widely used rootstock in nursery production, is found susceptible to the Phytophthora spp. Hence, the present study was carried out to evaluate antagonistic activity of Trichoderma spp. isolates against Phytophthora nicotianae var. parasitica causing foot rot in C. jambhiri under lab and net-house conditions. Seven isolates (parent and mutant) of Trichoderma spp. were tested in vitro. Amongst them, T20 mutant (Trichoderma asperellum) exhibited maximum mycoparasitism, volatile activity and non-volatile activity, i.e. 83.70%, 79.26% and 84.81%, respectively. The same T20 mutant (T. Asperellum) also showed maximum glucanase activity, i.e. 1.98 unit/ml. Further, talc-based bio formulations of T. asperellum T20 isolate (parent and mutant) were tested under net-house conditions over a period of two years (2016–2017 and 2017–2018) at the research farm of Punjab Agricultural University, Ludhiana, Punjab. Amongst all the treatments, the application of T20 mutant (T. asperellum) (seed + soil 15 g) had minimum disease incidence (13.33%), maximum disease control (83.30%) and maximum growth promotion i.e. shoot length (37.67 cm) and root length (30.67 cm). Based on our findings, T. asperellum T20 mutant strain used as seed + soil treatment was able to effectively manage the foot rot, in C. jambhiri nursery under net-house conditions and also promoted the plant growth.